Stimulatory effect of magnetite on the syntrophic metabolism of Geobacter co-cultures: Influences of surface coating. (1st July 2019) - You, Yunshen; Zheng, Shiling; Zang, Hongmei; Liu, Feng; Liu, Fanghua; Liu, Juan
Abstract: Magnetite-mediated direct interspecies electron transfer (DIET) can facilitate syntrophic metabolism in natural microbial communities and also promote the performance of the engineered systems based on syntrophic interactions. In this study, the stimulatory effect of bare synthetic magnetite (Mt), humic acid coated magnetite, and SiO2 coated magnetite (Mt-SiO2 ) on DIET in defined co-cultures of Geobacter metallireducens / Geobacter sulfurreducens were studied. Magnetite coated with Aldrich humic acid (HA) and Elliott Soil humic acid (HAES ), respectively, were prepared, and the two kinds of humic acid influenced the ability of Mt to promote syntrophic metabolism of the co-cultures in a similar way. When weight concentration was the same, pure humic acid presented the stimulatory effect on DIET similar to bare magnetite. However, the presence of HA coating on magnetite surface caused 50% and 61%, respectively, decrease in the rates of ethanol consumption ( Re ) and succinate production ( Rs ) in DIET processes. Pure HA in the same weight concentration as the HA coating in Mt-HA induced the similar metabolism rates as Mt-HA. In the Mt-HA mediated DIET, most electrons from ethanol metabolism were transferred to G. sulfurreducens selectively through the HA coating, and magnetite core hardly contributed to DIET processes. The SiO2 coating on magnetite resulted in 81% and 89%, respectively, decreases in Re and Rs, mainly because the non-conductive SiO2 layer hindered electron transfer between magnetite core and bacteria. After eight-day incubation with the co-cultures, bare magnetite nanoparticles formed relatively larger and more compact aggregates with cells than Mt-HA and Mt-SiO2, due to the different surface charge between bare and coated Mt. The generation of dissolved Fe(II) and HCl-extractable Fe(II) due to microbial reduction of magnetite by G. metallireducens and vivianite formation were observed along with DIET processes in all DIET experiments. Based on these results, different pathways of electron transfer in defined co-cultures of Geobacters with bare and coated magnetite nanoparticles were proposed. The findings in this study demonstrate the significant effects of surface properties on the ability of magnetite to stimulate DIET, which needs to be considered in order to comprehensively understand the role and mechanisms of mineral-mediated DIET in natural and engineered systems.